An ambient temperature dependent small signal model of GaN HEMT using method of curve fitting. Issue 12 (7th September 2020) - Majumdar, Arijit; Chatterjee, Soumyo; Chatterjee, Sayan; Chaudhari, Sheli Sinha; Poddar, Dipak Ranjan
Abstract: In this article, ambient temperature effect on small signal model of AlGaN/GaN HEMT has been explored. Based on the study, an analytical method to understand the ambient temperature dependence on device behavior has been developed. Effectiveness of the proposed method has been illustrated through comparison with measured data. Moreover, comparison with other analytical methods has also been carried out illustrating its acceptability threshold.